What pasts does VoD narrate? Times, spaces and agents present in the Netflix catalog (as seen from Mexico) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
The consolidation of a medium implies a reordering of the ways of producing meaning. One of them, of importance in the conformation of collective identities, is the way in which our common past is narrated. In VoD systems, this implies pasts that transcend the local to position themselves as transnational memories. In this text, we propose to think of Netflix as a relevant agent of cultural memory. Returning to some principles on the mediations of memory, we propose the analysis of part of the catalog of productions, to analyze the relationship between positioning strategies and ways of constructing pasts, as seen from Mexico. Taking as variables the times, spaces and agents represented, the analysis allows us to reflect on the idea of cultural proximity as an element to be taken into account in the constitution of these memory media.
Keywords: Netflix, memory, fiction, past